1962
DOI: 10.2136/sssaj1962.03615995002600040025x
|View full text |Cite
|
Sign up to set email alerts
|

Response of Slash Pine to Nitrogen and Phosphorus Fertilization

Abstract: A slash pine plantation in the lower Coastal Plain of Georgia was fertilized at age 9 with 200 pounds per acre of N, 44 pounds per acre of P, and with both elements. Diameter and basal area growth response to N was obtained for each of the first 3 years following treatment, but maximum stimulation occurred the year after fertilization. Diameter growth of the largest 400 trees per acre was also significantly increased by N treatment. P supplements gave no response in the deep sandy soil. Height growth responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1965
1965
1999
1999

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…On poorer soils the addition of nitrogen has occasionally resulted in faster growth of old forests. Walker & Youngberg (1962) found that slash pine plantations approximately 9 m. tall increased significantly in diameter growth when fertilized with nitrogen whilst phosphorus supplements gave no response. B.S.P.…”
Section: ( D ) Use Of Chemical Jertilizm-smentioning
confidence: 96%
See 1 more Smart Citation
“…On poorer soils the addition of nitrogen has occasionally resulted in faster growth of old forests. Walker & Youngberg (1962) found that slash pine plantations approximately 9 m. tall increased significantly in diameter growth when fertilized with nitrogen whilst phosphorus supplements gave no response. B.S.P.…”
Section: ( D ) Use Of Chemical Jertilizm-smentioning
confidence: 96%
“…The nitrogen applications increased height growth from two to three times in all height classes, with the largest trees showing the greatest responses and the site quality class improved from class V to 111 or better. Walker & Youngberg (1962) found that slash pine plantations approximately 9 m. tall increased significantly in diameter growth when fertilized with nitrogen whilst phosphorus supplements gave no response. Mayer-Krapoll ( 1956), from European experience with the fertilization of forests of standard trees, also stresses the importance of nitrogen and suggests that on sites without a raw humus layer, 20-40 kg.…”
Section: ( D ) Use Of Chemical Jertilizm-smentioning
confidence: 96%